Aerodynamic characterisation of model tree canopies in a wind tunnel (Science of The Total Environment, 1994)
The aerodynamic characteristics of ‘model’ tree canopies within a wind tunnel are reported. Wind speed profiles above and within canopies comprising Norway spruce (Picea abies) and Holm oak (Quercus ilex) saplings were determined by hot wire and hot film anemometry at a free-stream air velocity subsequently used for experiments on the dry deposition of aerosol particles to both canopies. Friction velocities (U∗) of 128 and 104 cm s−1 were observed for Norway spruce and Holm oak, respectively. Vertical distributions of wind speed (U) and turbulence intensity (i) within the canopies were similar in form and magnitude to those reported in the literature for full-sized forest canopies, suggesting that the sapling canopies provide a realistic ‘model’ with which to investigate the process of dry deposition.

AERODYNAMIC CHARACTERIZATION OF MODEL TREE CANOPIES IN A WIND-TUNNEL (SCIENCE OF THE TOTAL ENVIRONMENT, 1994)
The aerodynamic characteristics of `model' tree canopies within a wind tunnel are reported. Wind speed profiles above and within canopies comprising Norway spruce (Picea abies) and Holm oak (Quercus ilex) saplings were determined by hot wire and hot film anemometry at a free-stream air velocity subsequently used for experiments on the dry deposition of aerosol particles to both canopies. Friction velocities (U{*}) of 128 and 104 cm s-1 were observed for Norway spruce and Holm oak, respectively. Vertical distributions of wind speed (U) and turbulence intensity (i) within the canopies were similar in form and magnitude to those reported in the literature for full-sized forest canopies, suggesting that the sapling canopies provide a realistic `model' with which to investigate the process of dry deposition.